Female Demons in the Fantasies of George MacDonald - Pepper, Letitia Sheila (My University, 1980)
The thesis analyses several female characters in the fantasies of George MacDonald, using the concept of Jungian archetypes as a basis for study and comparison. Various similarities and contrasts between individual figures are developed first among those representing the "good" aspect of the Feminine and then the "evil". Some attempt is made to link the techniques used in the fantasy characterizations with those used by MacDonald in his "realistic" novels.
Keywords: English; English Language and Literature; English Language and Literature